Pengaruh Penambahan Labu Waluh (Labu Kuning) Terhadap Karakteristik Kimia dan Organoleptik Mie Kering - Putri, Meta Atika; Kawuri Putri , Satiti; Aisah, Aisah (Prosiding Seminar Kesehatan Nasional, 2024)
Pumpkins has advantages when chosen as a processed food ingredient, including : complete nutrition, as a natural coloring and high productivity. The nutrients contained in quining pumpkin are carbohydrate, sveral types of vitamins (A,C, B3, B6, K, niacin, thiamine and riboflavin), dietary fiber such as : pektin, β-karoten, tokoferol and several types of minerals. The β-karoten content in quining pumpkin can also replace the use of coloring (methanil yellow) in the noodle making process. Therefore, pumpkin is a nutritional source with great potential to be developed as an alternative raw material to substitute wheat flour in making various types of noodles including dry noodles.This study uses an experimental research method with the type of RAL which consists of four pumpkin addition treatments namely 0%, 20%, 25% and 30%. This research aims to detrmine the effect of adding pumpkin on chemical characteristics and organoleptic quality of dry noodles. The organoleptic test was carried out by 30 panelists then the organoleptik test result will be analyzed using SPSS One-way ANOVA and Tukey’s test. The results showed that the addition of pumpkin significaly affected organoleptic quality which included color, tekture, taste, overall acceptance, protein content, carbohydrate content, but the water content has no real effect on dried noodles. The nest treatment of study was P4 (100% flour : 30% addition pumpkin) with characteristics of color 4.73 (likes), texture 3.76 (likes), aroma 3.70 (likes), taste 3.96 (likes) with protein content 10.03% bb, carbohydrate content 73.61% bb, and water content 14.01%. In this research, it can be concluded that the addition of pumpkin has a significant effect on the acceptability of the aroma and texture of dry noodles and has no real effect on the aroma and taste of the dry noodles produced, while the nutritional content of dry noodles meets SNI 8217-2015 standards.